2015
DOI: 10.3390/md13085297
|View full text |Cite
|
Sign up to set email alerts
|

Silaffins in Silica Biomineralization and Biomimetic Silica Precipitation

Abstract: Biomineralization processes leading to complex solid structures of inorganic material in biological systems are constantly gaining attention in biotechnology and biomedical research. An outstanding example for biomineral morphogenesis is the formation of highly elaborate, nano-patterned silica shells by diatoms. Among the organic macromolecules that have been closely linked to the tightly controlled precipitation of silica in diatoms, silaffins play an extraordinary role. These peptides typically occur as comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(101 citation statements)
references
References 233 publications
(312 reference statements)
2
99
0
Order By: Relevance
“…Silaffins, for example, are protein constituents of biosilica, playing an active role in silica formation. These small proteins with numerous phosphoserine repeats self-assemble via electrostatic interactions; a prerequisite for biosilica formation [110,111]. SM50, from the mineralized larval of sea urchin spicules, contains C-type lectin and IDPs repeat domains.…”
Section: Intrinsically Disordered Proteins (Idps)mentioning
confidence: 99%
“…Silaffins, for example, are protein constituents of biosilica, playing an active role in silica formation. These small proteins with numerous phosphoserine repeats self-assemble via electrostatic interactions; a prerequisite for biosilica formation [110,111]. SM50, from the mineralized larval of sea urchin spicules, contains C-type lectin and IDPs repeat domains.…”
Section: Intrinsically Disordered Proteins (Idps)mentioning
confidence: 99%
“…In vitro , large amounts of proteins can be properly encapsulated in silica by simply mixing cationic catalyst with the silicic acid and the protein itself7 or, to increase the immobilization yield, the protein can be fused to a biosilica-promoting peptide891011121314. The materials obtained by such natural processes can be easily tuned into different morphologies by the use of slight perturbations of the experimental conditions1015, and can be easily endowed with peculiar chemical properties, such as fluorescence or catalytic activity by the incorporation of proteins9. In turn, proteins that are entrapped in a silicic matrix become more stable and easily reusable1617.…”
mentioning
confidence: 99%
“…To better understand and characterize key elements in biosilica formation and their functional pathway SSNMR studies of peptides such as R5 and LKα free and bound to silica were carried out. R5 (SSKKSGSYSGSKGSKRRIL) is a short derivative of silaffin from C. fusiformis lacking PTM that catalyzes silica formation in vitro [44,147,33]. Some studies indicated that the R5 peptide self-assembles and forms aggregates that provide templates for silica formation [148][149][150], while others found no evidence of self-assembly and hypothesize that silica formation occurs through salt-bridges.…”
Section: Nmr Characterization Of Diatomsmentioning
confidence: 97%
“…To fruitfully put this lesson to use, bioinspired matrices have been developed such as biosilica. The definition of biosilica, just like that of biomaterials in general, varies between silica/materials that are formed in nature by living organisms (aka biogenic materials, which are more appropriately referred to as biosilica) and silica/materials that is synthesized in the lab by bioinspired reactions, using molecules from the living organism or their derivatives [32][33][34], to mimic the "natural conditions" (bio-inspired silica). Hereon, for simplicity we will refer to either species as biosilica, as the origin of the material is clearly described along with the experimental details.…”
Section: Biosilica -A Lesson To Be Learnedmentioning
confidence: 99%